Menurunkan Loss Time dengan Meningkatkan Efektivitas Laporan Harian Operator - Frenaldi Chandra; Benedictus Rahardjo (Jurnal Titra, 2017)
The current problem in PT. XYZ is the line stop on Drive Chain assembly which causes loss time. Data of problems and loss time written in operator daily report is not actually representing all the actual problems and loss time, it makes the decision of fixing problem incorrect. The other problem is the corrective actions which have already done for the problems in operator daily report, but the same problem always happens. PT. XYZ wants to know whether the real root causes of the problems in assembling are caused by current problem or others. PT. XYZ also wants to know the problem that causes largest loss time. Method used to identify root causes of the problems is Fishbone diagram and Method used to identify problem that causes largest loss time is Pareto diagram. The improvement for these problems are fixing the operator daily report, added counting tool, fixing the location of writing in operator daily report, and added sheet to recap problems and loss time.